The Influence of Additives and Environment on Biodegradation of PHBV Biocomposites - Brdlík, Pavel; Borůvka, Martin; Běhálek, Luboš; Lenfeld, Petr (Polymers, 2022)
The biodegradation of polyhydroxybutyrate-co-hydroxyvalerate (PHBV) ternary biocomposites containing nature-based plasticizer acetyl tributyl citrate (ATBC), heterogeneous nucleation agents-calcium carbonate (CaCO3) and spray-dried lignin-coated cellulose nanocrystals (L-CNC)-in vermicomposting, freshwater biotope, and thermophilic composting have been studied. The degree of disintegration, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and the evaluation of surface images taken by scanning electron microscopy (SEM) were conducted for the determination influence of different environments and additives on the biodegradation of PHBV. Furthermore, the method adapted from ISO 14855-1 standard was used for thermophilic composting. It is a method based on the measurement of the amount of carbon dioxide evolved during microbial degradation. The highest biodegradation rate was observed in the thermophilic condition of composting. The biodegradation level of all PHBV-based samples was, after 90 days, higher than 90%. Different mechanisms of degradation and consequently different degradation rate were evaluated in vermicomposting and freshwater biotope. The surface enzymatic degradation, observed during the vermicomposting process, showed slightly higher biodegradation potential than the hydrolytic attack of freshwater biotope. The application of ATBC plasticizers in the PHBV matrix caused an increase in biodegradation rate in all environments. However, the highest biodegradation rate was achieved for ternary PHBV biocomposites containing 10 wt. % of ATBC and 10 wt. % of CaCO3. A considerable increase in the degree of disintegration was evaluated, even in freshwater biotope. Furthermore, the slight inhibition effect of L-CNC on the biodegradation process of ternary PHBV/ATBC/L-CNC could be stated.
Keywords: vermicomposting; biodegradation; thermophilic composting; freshwater biotope; additives; polyhydroxybutyrate-co-hydroxyvalerate